Efektivitas Pajak Hotel dan Kontribusinya terhadap Pendapatan Asli Daerah di Yogyakarta Tahun 2018-2023 - Wahadah, Tri Nur; Kurnianingsih, Retno (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze how the effectiveness and contribution of hotel tax to local revenue in Yogyakarta in 2018-2023. Using quantitative methods. Source of data from the Regional Financial and Asset Management Agency (BPKAD) of Yogyakarta city from 2018-2023 which is secondary data. Sampling technique with cluster sampling. The results of this study, the effectiveness of hotel tax for the period 2018-2023 is classified as very effective. However, hotel taxes that contribute to Local Revenue in 2018, 2019, 2022, and 2023 are classified as very good with achievements of more than 20%. Meanwhile, in 2020 it is classified as quite good, namely 13.90% and in 2021 it is 11.63% which is classified as moderate. Therefore, it is recommended that future researchers expand the research object and use other sampling techniques.